Band 3 profile as a marker of erythrocyte changes in chronic kidney disease patients - Costa, Elísio (2010)
Our aim was to study changes in red blood cell (RBC) membrane band 3 profile, as a cumulative marker of RBC changes, in chronic kidney disease (CKD) patients under haemodialysis and recombinant human erythropoietin (rhEPO) therapy and its linkage with resistance to this therapy. We studied 63 CKD patients, 32 responders and 31 non-responders to rhEPO therapy, and 26 healthy individuals. We evaluated the band 3 profile [% of band 3 monomer, high molecular weight aggregates (HMWAg), and proteolytic fragments (Pfrag)], membrane-bound haemoglobin (MBH), haematological data, total serum bilirubin, glutathione peroxidase (GPx) and superoxide dismutase activities, total antioxidant status (TAS) and plasma lipid peroxidation (TBA). Compared to controls, band 3 profile presented by CKD patients showed statistically significant lower HMWAg and Pfrag values and a significant higher value in band 3 monomer. GPx, TBA and TAS activities, and TBA/TAS ratio were also significantly higher in CKD patients. Comparing responders to non-responders CKD patients, significantly lower value in Pfrag and a trend for a higher value in MBH were found in non-responders. Our data suggest that CKD patients present younger RBC population, which could be related to the rhEPO therapy. The adverse plasma environment associated to CKD patients under hemodialysis imposes changes in band 3 profile, particularly in non-responders, suggesting that resistance to rhEPO therapy in CKD patients seems to be associated to an increase in RBC damage.